A Scribal Solution to a Problematic Measurement in the Apocalypse - Hernández, Juan (New Testament studies, 2010)
Orthographic variation within the manuscripts of the Greek NT is seldom a cause célèbre beyond the ranks of diehard textual critics. Even among these most will concede that orthographic irregularities amount to little more than evidence of scribal incompetency or inconsistency in their spelling practices. To find the same word both spelled correctly and misspelled within a single manuscript by the same scribe is not uncommon. It approaches the norm. The critical editions of our Greek NTs have therefore opted, on good grounds, to exclude textual variants displaying non-standardized spelling. To include them would make it impossible for anyone to use the critical apparatuses in a meaningful way. The deluge of senseless errors would drown out variants of demonstrable textual significance.